A randomized trial to evaluate the effectiveness of an individual, education-based safe transport program for drivers aged 75 years and older - Keay, Lisa (BioMed Central, 2013)
BACKGROUND: There are concerns over safety of older drivers due to increased crash involvement and vulnerability to injury. However, loss of driving privileges can dramatically reduce independence and quality of life for older members of the community. The aim of this trial is to examine the effectiveness of a safe transport program for drivers aged 75 years and older at reducing driving exposure but maintaining mobility. METHODS AND DESIGN: A randomised trial will be conducted, involving 380 drivers aged 75 years and older, resident in urban and semi-rural areas of North-West Sydney. The intervention is an education program based on the Knowledge Enhances Your Safety (KEYS) program, adapted for the Australian context. Driving experience will be measured objectively using an in-vehicle monitoring device which includes a global positioning system (GPS) to assess driving exposure and an accelerometer to detect rapid deceleration events. Participation will be assessed using the Keele Assessment of Participation (KAP). Data will be analysed on an intention-to-treat basis; the primary outcomes include driving exposure, rapid deceleration events and scores for KAP. Secondary outcomes include self-reported measures of driving, socialisation, uptake of alternative forms of transport, depressive symptoms and mood. A detailed process evaluation will be conducted, including examination of the delivery of the program and uptake of alternative forms of transport. A subgroup analysis is planned for drivers with reduced function as characterized by established cut-off scores on the Drivesafe assessment tool. DISCUSSION: This randomised trial is powered to provide an objective assessment of the efficacy of an individually tailored education and alternative transportation program to promote safety of older drivers but maintain mobility. Trial registration: Australian New Zealand Clinical Trials Registry ACTRN12612000543886.